2016
DOI: 10.1111/jnc.13680
|View full text |Cite
|
Sign up to set email alerts
|

The scaffold protein calcium/calmodulin‐dependent serine protein kinase controls ATP release in sensory ganglia upon P2X3 receptor activation and is part of an ATP keeper complex

Abstract: P2X3 receptors, gated by extracellular ATP, are expressed by sensory neurons and are involved in peripheral nociception and pain sensitization. The ability of P2X3 receptors to transduce extracellular stimuli into neuronal signals critically depends on the dynamic molecular partnership with the calcium/calmodulin-dependent serine protein kinase (CASK). The present work used trigeminal sensory neurons to study the impact that activation of P2X3 receptors (evoked by the agonist a,b-meATP) has on the release of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…In particular, activation of Panx1 through the P2x71230, P2x331, and P2x432 receptors have been shown to lead to maturation and release of pro-inflammatory mediators, thereby sensitizing peripheral and spinal cord neurons3132. We found that behavioral hypersensitivity in our orofacial pain model is accompanied by increased Panx1 expression and that neurons and GFAP-positive glia in the trigeminal ganglia become hyper-excitable.…”
Section: Discussionmentioning
confidence: 57%
“…In particular, activation of Panx1 through the P2x71230, P2x331, and P2x432 receptors have been shown to lead to maturation and release of pro-inflammatory mediators, thereby sensitizing peripheral and spinal cord neurons3132. We found that behavioral hypersensitivity in our orofacial pain model is accompanied by increased Panx1 expression and that neurons and GFAP-positive glia in the trigeminal ganglia become hyper-excitable.…”
Section: Discussionmentioning
confidence: 57%
“…Because R192Q KI cultures at baseline express a higher number of potential pore-forming cells [18] and release cytokines, ATP and CGRP [16,18,40], the overall higher membrane permeability in R192Q KI trigeminal cultures was consistent with the expected R192Q KI phenotype. In addition, CGRP, which is a trigger for migraine pain [41] and neuronal sensitisation [26] via immunomodulatory functions [42], potentiated fluorescence responses in a wider number of cells in R192Q KI culture rather than in WT one.…”
Section: Role Of Cgrp In Pore Formation Activitymentioning
confidence: 63%
“…Because α,β-meATP evokes the release of endogenous ATP from neurons via a Pannexin 1-mediated mechanism [40], the application of this agonist induced a fluorescence signal that we may attribute to activation of a wider P2X receptor population following by ATP priming. The reason for the smaller effect of Dashed line indicates WT control values, taken as 100%.…”
Section: P2x7 Receptors Of Tg Culturesmentioning
confidence: 91%
“…Interestingly, ATP release through pannexin was also shown to be induced downstream of P2X3 activation in trigeminal sensory neurons. This calcium/calmodulin‐dependent ATP efflux pathway potentially drives feedforward potentiation of painful signals (Bele and Fabbretti, ).…”
Section: P2x3 and P2x2/3 Receptors In Primary Sensory Neuronsmentioning
confidence: 99%